2019
DOI: 10.1098/rsbl.2019.0564
|View full text |Cite
|
Sign up to set email alerts
|

Audio–visual crossmodal correspondences in domestic dogs ( Canis familiaris )

Abstract: Crossmodal correspondences are intuitively held relationships between non-redundant features of a stimulus, such as auditory pitch and visual illumination. While a number of correspondences have been identified in humans to date (e.g. high pitch is intuitively felt to be luminant, angular and elevated in space), their evolutionary and developmental origins remain unclear. Here, we investigated the existence of audio–visual crossmodal correspondences in domestic dogs, and specifically, the known human correspon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…The data is available on Dryad and is accessible under the following link: [36]. The data are provided in the electronic supplementary material [37].…”
Section: Data Accessibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The data is available on Dryad and is accessible under the following link: [36]. The data are provided in the electronic supplementary material [37].…”
Section: Data Accessibilitymentioning
confidence: 99%
“…Another reason why dogs are a good candidate for our investigation is the fact that recently we found that they show evidence for a crossmodal correspondence between acoustic pitch and elevation (spatial height). In our earlier study, they preferentially attended to pitch-elevation pairings that were congruent , as opposed to incongruent [23]—where ‘congruency’ is defined as matching human intuition (i.e. congruent = high-pitched sounds were associated with high spatial elevation, and low-pitched sounds with objects near the ground; incongruent = the reverse).…”
Section: Introductionmentioning
confidence: 99%
“…A recent line of research focused on the existence of crossmodal correspondences in non-human animals, providing positive evidence in several cases, all within the clade of mammals. For instance, both humans and chimpanzees associate high luminosity with high pitch sounds and low luminosity with low pitch sounds [ 10 ]; rhesus monkeys associate spatial proximity with high pitch sounds and further distance with low pitch sounds [ 11 ]; dogs associate elevated and low spatial positions, and small and large dimensions, with high and low pitch, respectively [ 12 , 13 ]. This congruous body of evidence suggests that crossmodal correspondences might be a mechanism shared among mammals.…”
Section: Introductionmentioning
confidence: 99%
“…There is ongoing debate regarding the ubiquity and universality of a correspondence between spatial height and auditory pitch across cultures (e.g., Dolscheid et al, 2013Dolscheid et al, , 2020Evans & Treisman, 2010;Korzeniowska et al, 2019;Majid et al, 2018;Parise et al, 2014;Parkinson et al, 2012;Shayan et al, 2011;Starr & Srinivasan, 2018). In this study, we used a multimodal communication paradigm in which dyads listened to individual sounds and short melodies and described what they heard to their partner.…”
Section: Discussionmentioning
confidence: 99%
“…Sound and space are closely connected in language and thought, but the exact nature of this relationship is disputed. Adults and children from the earliest ages respond to correspondences between auditory pitch and various spatial dimensions (Dolscheid, Hunnius, Casasanto, & Majid, 2014; Marks, Hammeal, Bornstein, & Smith, 1987; Möhring, Ramsook, Hirsh‐Pasek, Golinkoff, & Newcombe, 2016; Roffler & Butler, 1968; Rusconi, Kwan, Giordano, Umilta, & Butterworth, 2006; Starr & Srinivasan, 2018; Walker et al., 2010, 2018)—as do non‐human animals, specifically dogs (Korzeniowska, Root‐Gutteridge, Simner, & Reby, 2019)—suggesting there is an inherent connection between these domains. Consistent with this, across the world's languages, spatial metaphors for pitch are ubiquitous (Eitan & Timmers, 2010; Majid et al., 2018).…”
Section: Introductionmentioning
confidence: 99%